Influence of activator on meiosis of tomato (Lycopersicon esculentum Mill.) (Bangladesh Journal of Botany, 2014)
The cytogenetic effects of activator Act-2 (based in compounds of addition hydro soluble of K-vitamin group a new and specific organic metabolic activator) on meiosis of tomato (Lycopersicon esculentum Mill.) were studied. The activator was applied to tomato plant grown in greenhouse at the dosage (150 cc/100 water) recommended by the manufacturing company and double the recommended dosage (300 cc/100 water) as well. It was observed that all dosages of the activator gave rise to some changes in cell shapes, chromosome structures, cell division patterns and cell sizes of tomato pollen. As a consequence of chromosomal anomalies sterile pollens were produced that affected yield negatively. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18045 Bangladesh J. Bot. 42(2): 361-365, 2013 (December)